Bibliografia prac Roberta Elsie. (Teksty naukowe. Tłumaczenia. Opracowania. Wystąpienia) - Irena Sawicka (Slavia Meridionalis, 2018)
A bibliography of works by Robert Elsie. (Scientific papers, translations, studies, presentations)